Brain Tuberculomas as BCGitis Complication Presenting with Epileptic Spasms: A Case Report - Ayadi, Basma; Kamoun Feki, Fatma; Ben Nsir, Siham; Bouchaala, Wafa; Mnif, Zeineb; Ben Jemaa, Mounir; Triki, Chahnez (Journal of Pediatric Neurology, 2020)
Central nervous system (CNS) BCGitis is a rare but a very severe complication of the Bacille Calmette–Guerin (BCG) vaccine. It could be a diagnostic challenge that may lead to a delay in treatment. A 5-month-old boy presented with infantile spasms, had posted natal BCG vaccination and developed brain tuberculomas as brain BCGitis. Laboratory findings were normal. He received 14 months of antitubercular regimen with good tolerance and both clinical and radiological improvement. The main difficulty in brain BCGitis is to make a diagnosis that requires histological or bacteriological examination. A good evolution without sequel could be seen if it is treated early.
Keywords: epileptic spasms; BCGitis; brain tuberculomas; child